Piglet meets a heffalump - Milne, A. A. (Alan Alexander), 1882-1956.; Shepard, Ernest H. (Ernest Howard), 1879-1976 (New York : Dutton Children's Books, 1993)
Piglet and Pooh set out to trap a heffalump.
Keywords: Toys -- Fiction